Altered Sleep-Related Consolidation and Neurocognitive Comorbidity in CECTS - Georgopoulou, Victoria; Spruyt, Karen; Garganis, Kyriakos; Kosmidis, Mary H. (Frontiers in Human Neuroscience, 2021)
Our aim is to use neurophysiological sleep-related consolidation phenomena to identify putative pathophysiological mechanisms in CECTS linked to diffuse neurocognitive deficits. We argue that there are numerous studies on the association between seizure aspects and neurocognitive functioning but not as many on interictal variables and neurocognitive deficits. We suggest two additional foci. First, the interictal presentation in CECTS and second, neuronal oscillations involved in sleep-related consolidation processes. Existing data on mechanisms through which interictal epileptiform spikes impact upon sleep-related consolidation indicate that they have the potential to: a) perturb cross-regional coupling of neuronal oscillations, b) mimic consolidation processes, c) alter the precision of the spatiotemporal coupling of oscillations, and d) variably impact upon sleep-related consolidation performance. Sleep spindles merit systematic study in CECTS in order to clarify: a) the state of the slow oscillations with which they coordinate, b) the precision of slow oscillation-spindle coupling, and c) whether their developmental trajectories differ from those of healthy children. We subsequently review studies on the associations between IES load during NREM sleep and sleep-related consolidation performance in childhood epilepsy. We then use sleep consolidation neurophysiological processes and their interplay with IES to help clarify the diffuse neurocognitive deficits that have been empirically documented in CECTS. We claim that studying sleep-related consolidation in CECTS will help to clarify pathophysiological mechanisms towards diverse neurocognitive deficits. Future developments could include close links between the fields of epilepsy and sleep, as well as new therapeutic neurostimulation targets.